Connecting material, preparation method thereof, bolt and application
By placing the carbon material in a strong acid and mixing it with the titanium alloy to form a modified connecting material, the problem of heating and loosening of traditional carbon steel bolts in high voltage and high current environments is solved, the electromagnetic and mechanical properties of the connecting material are improved, and the stability and safety of the circuit connection are enhanced.
Patent Information
- Application Number
- CN202510353040.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-03-25
AI Technical Summary
Traditional carbon steel bolts are prone to abnormal heating and loosening in high voltage and high current environments, resulting in unstable circuit connections and posing safety hazards.
The modified connecting material is formed by placing the carbon material in a strong acid and mixing it with the titanium alloy. The method includes filtering the carbon material and mixing it with the organic material, heating and filtering, and then placing the titanium alloy in a modified solution for modification to form a connecting material with good binding strength.
This method improves the electromagnetic and mechanical properties of the connecting materials, reduces the penetration of the external magnetic field into the inside of the titanium alloy, has a good magnetic shielding effect, and enhances the stability and safety of the connection.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of alloy materials, and in particular to a connecting material and a preparation method thereof, a bolt and an application thereof. Background Art
[0002] In the power system, the stability and safety of circuit connection are very important. At present, circuit connection mainly relies on bolt fixing, which is done by treating the contact surface, ensuring the contact surface is clean and flat, and then fastening it with bolts.
[0003] Traditional bolts are made of carbon steel and will generate eddy current heating, especially in high voltage and high current environments. Due to the degradation of electromagnetic properties (such as resistivity, magnetic permeability) and mechanical properties (mass loss), abnormal heating and loosening are prone to occur, causing the fastening system to fail, and also leading to energy waste and joint heating safety accidents. Summary of the invention
[0004] Based on this, in order to improve the electromagnetic properties and mechanical properties of the connecting material, it is necessary to provide a connecting material and its preparation method, bolts and applications.
[0005] The present application provides a method for preparing a connecting material, comprising the following steps: placing the carbon material in a strong acid, wherein the strong acid comprises one or both of nitric acid and sulfuric acid, and filtering for the first time to prepare a first solid; Mixing the first solid with an organic material, wherein the organic material includes polyschiff base, heating to 70° C. to 90° C., and filtering for a second time to prepare a second solid; The titanium alloy is placed in a modifying solution, the modifying solution including the second solid.
[0006] In one embodiment, the titanium alloy further comprises the following steps before being placed in the modifying solution: The titanium alloy is used as an anode and placed in an electrolyte together with a cathode material for electrolytic treatment.
[0007] In one embodiment, the electrolytic treatment satisfies one or more of the following conditions: (1) The concentration of the metal salt in the electrolyte is 0.1 mol / L to 0.5 mol / L; (2) The current density in the electrolytic treatment is 240 mA / cm 2 -250mA / cm 2 ; (3) The voltage in the electrolysis treatment is 5V~120V; (4) The titanium alloy further includes a step of being placed in a cleaning solution before the electrolytic treatment, wherein the cleaning solution includes one or both of hydrofluoric acid and nitric acid; (5) The cathode material is selected from one or more of metal platinum, metal nickel, metal palladium and graphite.
[0008] In one embodiment, the step of placing the carbon material before the strong acid further comprises the following steps: The carbon material is subjected to a heat treatment, placed in a pretreatment solution with a pH value of 1 to 2, filtered, and dried.
[0009] In one embodiment, preparing the first solid satisfies one or more of the following conditions: (1) The ratio of the carbon material to the strong acid is (5-15) g: (10-30) mL; (2) The strong acid comprises sulfuric acid and nitric acid in a molar ratio of (1-5):1; (3) The carbon material is placed in the strong acid for 10 to 12 hours; (4) The temperature of the carbon material placed in the strong acid is 35°C to 45°C.
[0010] In one embodiment, the preparation of the second solid satisfies one or both of the following conditions: (1) The mass ratio of the first solid to the organic material is (0.1-2): (0.01-1); (2) The organic material further includes an organic solvent, wherein the organic material includes 0.5 to 5 parts of the polySchiff base and 10 to 20 parts of the organic solvent.
[0011] In one embodiment, one or both of the following conditions are met: (1) The titanium alloy is placed in the modified solution for 20 min to 30 min; (2) The titanium alloy comprises metal vanadium, metal titanium and metal aluminum.
[0012] The present application also provides a connecting material, which is prepared according to the above-mentioned preparation method.
[0013] Furthermore, the present application provides a bolt, comprising the connecting material as described above.
[0014] Furthermore, the present application also provides the use of the above-mentioned connecting material or the above-mentioned bolts in circuit connection.
[0015] The present application modifies the titanium alloy by placing it in a modified carbon material. The modified carbon material can form a bond with some active sites on the surface of the titanium alloy or form physical adsorption to modify the surface of the titanium alloy, and has good bonding strength. A uniform carbon material coating is formed on the surface of the titanium alloy. Charge transfer may occur at the interface between the carbon material and the titanium alloy, changing the magnetic field distribution and reducing the penetration of the external magnetic field into the interior of the titanium alloy, playing a certain magnetic shielding role, and improving the electromagnetic properties and mechanical properties of the connecting material. DETAILED DESCRIPTION
[0016] In order to facilitate understanding of the present application, the present application will be described more comprehensively below. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0017] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0018] The term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of the related listed items, wherein the any and all combinations include any combination of two related listed items, any more related listed items, or all related listed items. For example, "A and / or B" includes three parallel solutions: A, B, and "a combination of A and B".
[0019] In this article, unless otherwise specified, "one or more" means any one of the listed items or any combination of the listed items. Similarly, "one or more" and other expressions that mean "one or more" are also understood in the same way unless otherwise specified.
[0020] In this document, "further", "further", "particularly", "for example", "such as", "example", "for example", etc. are used for descriptive purposes, indicating that the previous and subsequent technical solutions are related in terms of the content covered, but should not be understood as limiting the previous technical solution, nor can they be understood as limiting the scope of protection of this document. In this document, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.
[0021] Herein, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If multiple "optional" items appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" item is independent of each other. In this application, descriptions such as "optionally contain", "optionally include", etc. mean "contain or not contain". "Optional component X" means that component X exists or does not exist, or means that component X is contained or not contained.
[0022] In this document, the terms "first", "second", "third", "fourth", etc. in "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0023] In this article, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0024] Herein, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values within the numerical interval is considered to be continuous and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when a numerical interval only refers to integers within the numerical interval, including the two endpoint integers of the numerical range, and each integer between the two endpoints, is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical ranges disclosed herein should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows broadly including numerical interval types such as percentage intervals, ratio intervals, and ratio intervals.
[0025] Herein, the term "room temperature" or "normal temperature" generally refers to 4°C~35°C, for example, 20°C±5°C. In some embodiments herein, "room temperature" or "normal temperature" refers to 10°C~30°C. In some embodiments herein, "room temperature" or "normal temperature" refers to 20°C~30°C.
[0026] In this article, if there are multiple steps involved in the method flow, unless there is a clear different description in this article, there is no strict order restriction for the execution of these steps, and they can be executed in other orders than described. Moreover, any step can include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but can be executed at different times, and their execution order is not necessarily sequential, but can be executed in turn, alternating or simultaneously with other steps or parts of sub-steps or stages of other steps.
[0027] The present application provides a method for preparing a connecting material, comprising the following steps S10 to S30: Step S10: placing the carbon material in a strong acid, the strong acid comprising one or both of nitric acid and sulfuric acid, filtering for the first time to prepare a first solid; Step S20: mixing the first solid with an organic material, the organic material including poly Schiff base, heating to 70° C. to 90° C., filtering for a second time, and preparing a second solid; Step S30: placing the titanium alloy in a modified solution, wherein the modified solution includes a second solid.
[0028] The present application modifies the titanium alloy by placing it in a modified carbon material. The modified carbon material can form a bond with some active sites on the surface of the titanium alloy or form physical adsorption to modify the surface of the titanium alloy, and has good bonding strength. A uniform carbon material coating is formed on the surface of the titanium alloy. Charge transfer may occur at the interface between the carbon material and the titanium alloy, changing the magnetic field distribution and reducing the penetration of the external magnetic field into the interior of the titanium alloy, playing a certain magnetic shielding role, and improving the electromagnetic properties and mechanical properties of the connecting material.
[0029] It can be understood that the above carbon material can be but is not limited to carbon nanotubes.
[0030] In a specific example, the step of placing the carbon material in a strong acid also includes the following steps S1: The carbon material is subjected to heat treatment, placed in a pretreatment solution with a pH value of 1 to 2, filtered, and dried.
[0031] Further, the temperature of the heating treatment is 450°C to 480°C, and the time of the heating treatment is 20 min to 30 min. Specifically, the temperature of the heating treatment can be, but is not limited to, 450°C, 455°C, 460°C, 465°C, 470°C, 475°C or 480°C.
[0032] The pretreatment liquid may be, but is not limited to, a 37% by mass hydrochloric acid aqueous solution. Specifically, the carbon material is heated, placed in a 37% by mass hydrochloric acid aqueous solution pretreatment liquid, and stirred and refluxed for 3 to 4 days.
[0033] It can be understood that after filtering and before drying in the above step S1, the filtered solid is also washed with water, specifically, the solid is repeatedly washed with distilled water until the pH value of the washing solution is neutral.
[0034] Further, the drying temperature is 70°C to 80°C, and the drying time is 10h to 12h. Specifically, the drying temperature may be, but is not limited to, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C. The drying time may be, but is not limited to, 10h, 10.5h, 11h, 11.5h or 12h.
[0035] Specifically, the above step S1 is to purify the carbon nanotubes, which can remove some volatile impurities, and can dissolve and remove metal impurities, etc., so as to obtain pure carbon nanotubes and improve the stability and reliability of their performance.
[0036] In a specific example, the ratio of the carbon material to the strong acid is (5-15) g: (10-30) mL. Further, the strong acid includes sulfuric acid and nitric acid in a molar ratio of (1-5): 1. Specifically, the strong acid may not be limited to a 98% by mass sulfuric acid aqueous solution and a 70% by mass nitric acid aqueous solution in a molar ratio of (2-4): 1.
[0037] In a specific example, the carbon material is placed in the strong acid for 10 h to 12 h. Specifically, the carbon material is placed in the strong acid for 10 h, 10.5 h, 11 h, 11.5 h or 12 h.
[0038] In a specific example, the temperature of the carbon material in the strong acid is 35° C. to 45° C. Specifically, the temperature of the carbon material in the strong acid may be, but is not limited to, 35° C., 36° C., 37° C., 38° C., 39° C., 40° C., 41° C., 42° C., 43° C., 44° C., or 45° C.
[0039] After the carbon material is placed in a strong acid, 200 mL to 250 mL of deionized water is added to dilute the strong acid, followed by a first filtration, and then washing with deionized water for 2 to 4 times, and drying to prepare a first solid.
[0040] Further, the drying temperature is 60°C to 70°C, and the drying time is 16h to 20h. Specifically, the drying temperature may be, but is not limited to, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C. The drying time may be, but is not limited to, 16h, 17h, 18h, 19h or 20h.
[0041] It can be understood that the introduction of oxygen-containing functional groups such as carboxyl groups on the surface of the carbon material, which may be but not limited to carbon nanotubes, provides more chemical reaction active sites on the surface of the carbon material, thereby improving the compatibility and bonding between the carbon material and the titanium alloy matrix.
[0042] In a specific example, in preparing the second solid, the mass ratio of the first solid to the organic material is (0.1~2):(0.01~1).
[0043] In a specific example, in the preparation of the second solid, the organic material further includes an organic solvent, and the organic material includes 0.5 parts to 5 parts of poly Schiff base and 10 parts to 20 parts of the organic solvent.
[0044] Further, the organic solvent may be, but is not limited to, one or both of thionyl chloride and N,N-dimethylformamide.
[0045] Specifically, the first solid is first mixed with the first organic solvent and stirred at 60°C to 70°C, and then polyschiff base and the second organic solvent are added and stirred at 70°C to 90°C in a protective gas atmosphere, and the solid is separated, washed and dried to prepare the second solid. It can be understood that N, N-dimethylformamide and ethanol are used for washing respectively.
[0046] Furthermore, the first stirring time is 20h~24h, and the second stirring time is 10h~12h.
[0047] Specifically, the first stirring time may be, but is not limited to, 20 h, 21 h, 22 h, 23 h or 24 h.
[0048] The second stirring time may be, but is not limited to, 10 h, 11 h or 12 h.
[0049] In a specific example, the mass ratio of the first organic solvent to the second organic solvent is (0.06 g ~ 0.1 g): (16 g ~ 18.5 g).
[0050] In a specific example, the drying temperature is 55° C. to 65° C., and the drying time is 20 h to 24 h.
[0051] Through further grafting treatment, the polyschiff base organic molecules are grafted onto the surface of the carbon material. The grafted carbon material surface can form a more complex and stable interaction with the titanium alloy surface, such as chemical bonding, physical entanglement, etc., thereby enhancing the bonding force between the carbon nanotubes and the titanium alloy, making the carbon nanotubes more firmly attached to the titanium alloy surface, not easy to fall off during application, and improving the stability and durability of the connecting material.
[0052] In a specific example, the titanium alloy further includes the following pretreatment step S3 of the titanium alloy before placing the titanium alloy in the modification solution step S30: The titanium alloy is used as an anode and placed in an electrolyte together with a cathode material for electrolytic treatment.
[0053] Furthermore, the pretreatment step S3 also includes, before the electrolytic treatment, grinding, polishing, first cleaning, drying and second cleaning in a cleaning solution in sequence on the surface of the titanium alloy. It can be understood that the cleaning solution includes one or both of hydrofluoric acid and nitric acid, and the second cleaning time is 5 minutes to 10 minutes.
[0054] Furthermore, the pretreatment step S3 further includes a third cleaning step after the electrolytic treatment.
[0055] Specifically, deionized water and anhydrous ethanol are used in sequence for the third cleaning. It can be understood that deionized water and anhydrous ethanol are used for washing 3 to 5 times respectively.
[0056] In a specific example, the concentration of the metal salt in the electrolyte is 0.1 mol / L to 0.5 mol / L. The concentration of the metal salt in the electrolyte may be, but is not limited to, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L or 0.5 mol / L.
[0057] In one specific example, the current density during the electrolysis process is 240 mA / cm 2 -250mA / cm 2 Specifically, the current density in the electrolytic treatment may be, but is not limited to, 240 mA / cm 2 , 241mA / cm 2 、mA / cm 2 , 242 mA / cm 2 , 243 mA / cm 2 , 244 mA / cm 2 , 245 mA / cm 2 , 246 mA / cm 2 , 247 mA / cm 2 , 248 mA / cm 2 , 249 mA / cm 2 or 250 mA / cm 2 .
[0058] In a specific example, the voltage in the electrolysis process is 5 V to 120 V. Specifically, the voltage in the electrolysis process may be, but is not limited to, 5 V, 10 V, 15 V, 20 V, 25 V, 30 V, 35 V, 40 V, 45 V, 50 V, 55 V, 60 V, 65 V, 70 V, 75 V, 80 V, 85 V, 90 V, 95 V, 100 V, 105 V, 110 V, 115 V, or 120 V.
[0059] In a specific example, the material of the cathode is selected from one or more of metal platinum, metal nickel, metal palladium and graphite. Preferably, the cathode is metal platinum.
[0060] In a specific example, the titanium alloy is placed in the modifying solution for 20 min to 30 min. Specifically, the titanium alloy is placed in the modifying solution for 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min or 30 min.
[0061] In a specific example, the composition of the titanium alloy includes metal vanadium, metal titanium, and metal aluminum.
[0062] The above-mentioned pretreatment of the titanium alloy can reduce its surface roughness and obtain a smooth and flat surface, which can effectively reduce surface defects and remove oxide scale, oil stains and other impurities on the surface of the titanium alloy, while forming a more stable oxide film on the surface to enhance corrosion resistance; through treatment in the electrolyte, the chemical composition and structure of the surface can be further changed, thereby improving its corrosion resistance in various environments, and at the same time having good electromagnetic properties and mechanical properties.
[0063] The present application also provides a connecting material, which is prepared according to the above-mentioned preparation method.
[0064] Furthermore, the present application provides a bolt, comprising the connecting material as described above.
[0065] Furthermore, the present application also provides the use of the above-mentioned connecting material or the above-mentioned bolts in circuit connection.
[0066] The present application is further described in detail below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are preferably referred to the guidance given in the present application, and can also be based on the experimental manuals or conventional conditions in the art, can also be based on the conditions recommended by the manufacturer, or refer to experimental methods known in the art.
[0067] In the following specific embodiments, the measured parameters of raw material components may have slight deviations within the range of weighing accuracy unless otherwise specified. For temperature and time parameters, acceptable deviations caused by instrument test accuracy or operation accuracy are allowed. "Normal temperature" refers to 25°C; "normal pressure" refers to 100KPa or 101KPa.
[0068] The titanium alloy used in the following embodiments and comparative examples is TC4 titanium alloy, specifically, the mass percentage of metal titanium (Ti) in the TC4 titanium alloy is about 90%, the mass percentage of metal aluminum (Al) is about 6%, the mass percentage of metal vanadium (V) is about 4%, and a small amount of other elements such as iron, oxygen, carbon, etc.
[0069] The preparation method of polyschiff base used in the following examples and comparative examples is as follows: dimethyl sulfoxide is added to equimolar 4,4'-diamino-3,3'-dichlorodiphenyl sulfone and terephthalaldehyde, respectively, and the mixture is stirred until completely dissolved and then mixed, and the mixture is slowly heated to 80°C under the protection of xenon gas, reacted for 4 hours, cooled, poured into water for precipitation, filtered, repeatedly dissolved with dimethyl sulfoxide, and precipitated with water, and finally dried in a vacuum drying oven at 60°C for 48 hours to obtain polyschiff base.
[0070] Example 1 (1) Pretreatment of titanium alloy: grinding, polishing, cleaning and drying the surface of titanium alloy in sequence; then placing it in an acid solution for 5 minutes; then placing it in an electrolyte with an initial current density of 240 mA / cm 2 , the voltage gradually increased from 5V to 100V, and TC4 titanium alloy was used as the anode and platinum sheet was used as the cathode; after the electrolysis was completed, it was washed with deionized water and anhydrous ethanol three times in sequence, and then naturally air-dried; The acid solution is prepared by mixing 10 mL of 35% hydrofluoric acid, 10 mL of 65% nitric acid and 80 mL of deionized water; the electrolyte is prepared by 0.3 mol / L sodium chloride, glycerol, anhydrous ethanol and deionized water, and the volume ratio is: 0.3 mol / L sodium chloride: glycerol: anhydrous ethanol: deionized water = 3:5:4:1; (2) Purification of carbon nanotubes: Place the carbon nanotubes in a muffle furnace at 450°C for 20 min, stir and reflux with 37% hydrochloric acid for 3 days, filter, wash repeatedly with distilled water until the pH is neutral, and finally dry in a vacuum drying oven at 70°C for 10 h. (3) Oxidation / carboxylation treatment of the purified carbon nanotubes: Pour 10 g of the purified carbon nanotubes into 20 mL of a mixed acid solution of 98% sulfuric acid solution and 65% nitric acid solution in a volume ratio of 3:1, heat it to 35°C in a water bath, and perform ultrasonic treatment for 10 h. Then, add 200 mL of deionized water to dilute it, filter it, wash it twice with deionized water, and finally dry it in a drying oven at 60°C for 16 h. (4) Modifying the carbon nanotubes after oxidation / carboxylation: Add 0.06 g of thionyl chloride to 0.5 g of the carbon nanotubes after oxidation / carboxylation, heat to 60 °C, stir for 20 h, cool, and then perform rotary evaporation. Then add 1.5 g of polyschiff base and 16 g of N, N-dimethylformamide, and heat to 70 °C at a heating rate of 2 °C / min under argon atmosphere. React for 10 h, cool, centrifuge and remove the upper solution. Wash the precipitate with N, N-dimethylformamide and ethanol three times in turn, and finally dry it in a vacuum drying oven at 55 °C for 20 h. (5) Add 20 mL of dimethyl sulfoxide solution to 5 g of the modified carbon nanotubes, then immerse the pretreated titanium alloy in the solution until the solution covers the titanium alloy, and perform ultrasonic treatment for 20 minutes to obtain the connecting material.
[0071] Example 2 (1) Pretreatment of titanium alloy: grinding, polishing, cleaning and drying the surface of titanium alloy in sequence; then placing it in an acid solution for 8 minutes; then placing it in an electrolyte with an initial current density of 245 mA / cm 2 , the voltage gradually increased from 5V to 100V, and TC4 titanium alloy was used as the anode and platinum sheet as the cathode; after the electrolysis was completed, it was washed with deionized water and anhydrous ethanol for 4 times in sequence, and then naturally air-dried; The acid solution is prepared by mixing 11 mL of 35% hydrofluoric acid, 12 mL of 65% nitric acid and 85 mL of deionized water; the electrolyte is prepared by 0.3 mol / L sodium chloride, glycerol, anhydrous ethanol and deionized water, and the volume ratio is: 0.3 mol / L sodium chloride: glycerol: anhydrous ethanol: deionized water = 3:5:4:1; (2) Purification of carbon nanotubes: Place the carbon nanotubes in a muffle furnace at 460°C for 25 min, stir and reflux with 37% hydrochloric acid for 4 days, filter, wash repeatedly with distilled water until the pH is neutral, and finally dry in a vacuum drying oven at 75°C for 11 h. (3) Oxidation / carboxylation treatment of the purified carbon nanotubes: Pour 12 g of the purified carbon nanotubes into 24 mL of a mixed acid solution of 98% sulfuric acid solution and 65% nitric acid solution in a volume ratio of 3:1, heat it to 40°C in a water bath, and ultrasonically treat it for 11 h. Then, add 230 mL of deionized water to dilute it and filter it. Then, wash it with deionized water for 3 times, and finally dry it in a drying oven at 65°C for 18 h. (4) Grafting treatment of the oxidized / carboxylated carbon nanotubes: add 0.08 g of thionyl chloride to 0.6 g of the oxidized / carboxylated carbon nanotubes, heat to 65 °C, stir for 22 h, cool, and then perform rotary evaporation. Then add 2.2 g of polyschiff base and 17 g of N,N-dimethylformamide, and heat to 75 °C at a heating rate of 3 °C / min under argon atmosphere. React for 11 h, cool, centrifuge and remove the upper solution. Wash the precipitate with N,N-dimethylformamide and ethanol four times in turn, and finally dry it in a vacuum drying oven at 60 °C for 22 h. (5) Add 28 mL of dimethyl sulfoxide solution to 5 g of the grafted carbon nanotubes, then immerse the pretreated titanium alloy in the solution until the solution covers the titanium alloy, and perform ultrasonic treatment for 25 minutes to obtain the connecting material.
[0072] Example 3 (1) Pretreatment of titanium alloy: grinding, polishing, cleaning and drying the surface of titanium alloy in sequence; then placing it in an acid solution for 10 minutes; then placing it in an electrolyte with an initial current density of 250 mA / cm 2 , the voltage gradually increased from 5V to 100V, and TC4 titanium alloy was used as the anode and platinum sheet was used as the cathode; after the electrolysis was completed, it was washed with deionized water and anhydrous ethanol for 5 times in sequence, and then naturally dried; The acid solution is prepared by mixing 12 mL of 35% hydrofluoric acid, 15 mL of 65% nitric acid and 90 mL of deionized water; the electrolyte is prepared by 0.3 mol / L sodium chloride, glycerol, anhydrous ethanol and deionized water, and the volume ratio is: 0.3 mol / L sodium chloride: glycerol: anhydrous ethanol: deionized water = 3:5:4:1; (2) Purification of carbon nanotubes: Place the carbon nanotubes in a muffle furnace at 480°C for 30 min, stir and reflux with 37% hydrochloric acid for 4 days, filter, wash repeatedly with distilled water until the pH is neutral, and finally dry in a vacuum drying oven at 80°C for 12 h. (3) Oxidation / carboxylation treatment of the purified carbon nanotubes: Pour 15 g of the purified carbon nanotubes into 28 mL of a mixed acid solution of 98% sulfuric acid solution and 65% nitric acid solution in a volume ratio of 3:1, heat it to 45°C in a water bath, and perform ultrasonic treatment for 12 h. Then, add 250 mL of deionized water for dilution and filter, wash it with deionized water 4 times, and finally dry it in a drying oven at 70°C for 20 h. (4) Grafting treatment of the carbon nanotubes after oxidation / carboxylation: add 0.1 g of thionyl chloride to 0.8 g of the carbon nanotubes after oxidation / carboxylation, heat to 70 °C, stir for 24 h, cool, and then perform rotary evaporation. Then add 3 g of polyschiff base and 18.5 g of N, N-dimethylformamide, and heat to 80 °C at a heating rate of 4 °C / min under argon atmosphere. React for 12 h, cool, centrifuge and remove the upper solution. Wash the precipitate with N, N-dimethylformamide and ethanol for 5 times, and finally dry it in a vacuum drying oven at 65 °C for 24 h. (5) Add 30 mL of dimethyl sulfoxide solution to 5 g of the grafted carbon nanotubes, then immerse the pretreated titanium alloy in the solution until the solution covers the titanium alloy, and perform ultrasonic treatment for 30 minutes to obtain the connecting material.
[0073] Example 4 Compared with Example 1, the difference is that the titanium alloy surface is not pretreated; the rest remains unchanged.
[0074] Comparative Example 1 Compared with Example 1, the difference is that only the carbon nanotubes are purified; the rest remain unchanged.
[0075] Comparative Example 2 Compared with Example 1, the difference is that only the titanium alloy is replaced by a carbon steel material, including about 90% by mass of iron (Fe), about 7% by mass of carbon (C), and a small amount of silicon (Si), manganese (Mn), sulfur (S), phosphorus (P) and other elements; the rest remains unchanged.
[0076] Magnetic susceptibility measurement: measured using a vibrating sample magnetometer; the results are shown in Table 1.
[0077] Corrosion resistance test: The samples were placed in a salt spray test chamber for testing, and their mass loss rate was calculated; the results are shown in Table 1.
[0078] Table 1 It can be seen from Table 1 that the absolute values of the magnetic susceptibility of Examples 1-4 are all greater than the absolute value of the magnetic susceptibility of Comparative Examples 1-2, especially the absolute value of the magnetic susceptibility of Example 1-3 is significantly greater than the absolute value of the magnetic susceptibility of Comparative Examples 1-2, indicating that the magnetic shielding performance of the connecting materials of Examples 1-3 is significantly improved compared with that of Comparative Examples 1-2. At the same time, the magnetic shielding performance of the connecting materials of Examples 1-3 is also improved compared with that of the connecting materials of Example 4.
[0079] It can be seen from Table 1 that the mass loss rate of Examples 1-4 is smaller than that of Comparative Example 1-2, and in particular, the mass loss rate of Example 1-3 is significantly smaller than that of Comparative Example 1-2, indicating that the corrosion resistance of the connecting materials of Examples 1-3 is significantly improved compared with that of Comparative Example 1-2. At the same time, the corrosion resistance of the connecting materials of Examples 1-3 is also improved compared with that of the connecting materials of Example 4.
[0080] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0081] The above embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the protection scope of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the protection scope of the claims attached to the present application. Therefore, the protection scope of the patent of this application shall be based on the content of the attached claims, and the description can be used to interpret the content of the claims.
Claims
1. A method for preparing a connecting material, characterized in that: The following steps are involved: placing the carbon material in a strong acid, wherein the strong acid comprises one or both of nitric acid and sulfuric acid, and filtering for the first time to prepare a first solid; Mixing the first solid with an organic material, wherein the organic material includes polyschiff base, heating to 70° C. to 90° C., and filtering for a second time to prepare a second solid; The titanium alloy is placed in a modifying solution, the modifying solution including the second solid.
2. The preparation method according to claim 1, characterized in that The titanium alloy further comprises the following steps before being placed in the modifying solution: The titanium alloy is used as an anode and placed in an electrolyte together with a cathode material for electrolytic treatment.
3. The preparation method according to claim 2, characterized in that: The electrolytic treatment satisfies one or more of the following conditions: (1) The concentration of the metal salt in the electrolyte is 0.1 mol / L to 0.5 mol / L; (2) The current density in the electrolytic treatment is 240 mA / cm 2 -250mA / cm 2 ; (3) The voltage in the electrolysis treatment is 5V~120V; (4) The titanium alloy further includes a step of being placed in a cleaning solution before the electrolytic treatment, wherein the cleaning solution includes one or both of hydrofluoric acid and nitric acid; (5) The cathode material is selected from one or more of metal platinum, metal nickel, metal palladium and graphite.
4. The preparation method according to claim 1, characterized in that: The carbon material is placed in the strong acid before the step of: The carbon material is subjected to a heat treatment, placed in a pretreatment solution with a pH value of 1 to 2, filtered, and dried.
5. The preparation method according to claim 1, characterized in that: The preparation of the first solid satisfies one or more of the following conditions: (1) The ratio of the carbon material to the strong acid is (5-15) g: (10-30) mL; (2) The strong acid comprises sulfuric acid and nitric acid in a molar ratio of (1-5):1; (3) The carbon material is placed in the strong acid for 10 to 12 hours; (4) The temperature of the carbon material placed in the strong acid is 35°C to 45°C.
6. The preparation method according to claim 1, characterized in that: The preparation of the second solid satisfies one or both of the following conditions: (1) The mass ratio of the first solid to the organic material is (0.1-2): (0.01-1); (2) The organic material further includes an organic solvent, wherein the organic material includes 0.5 to 5 parts of the polySchiff base and 10 to 20 parts of the organic solvent.
7. The preparation method according to any one of claims 1 to 6, characterized in that: One or both of the following conditions are met: (1) The titanium alloy is placed in the modified solution for 20 min to 30 min; (2) The titanium alloy comprises metal vanadium, metal titanium and metal aluminum.
8. A connecting material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 7.
9. A bolt, characterized in that: Comprising the connecting material as claimed in claim 8.
10. Use of the connection material according to claim 8 or the bolt according to claim 9 in circuit connection.
Citation Information
Patent Citations
Chiral poly(Schiff base) salt ternary composite wave absorbing material
CN105062092A
Method for preparing hydroxyapatite biological ceramic on surface of titanium alloy by sol-gel method
CN113248249A
Bilateral high-density chemical bonding directional induction method for thermal connection interface of metal and thermoplastic composite material
CN118744529A